KRITIK ATAS SIKAP TANPA PAMRIH (DISINTERESTED ATTITUDE) MELALUI SUDUT PANDANG VOYEURISTIK - Richardo Torang Manahan; Harsawibawa Albertus (Jurnal Ilmiah Global Education, 2023)
A work of art contains a stratified aesthetic element in accordance with the satisfaction of the human senses. Beauty is often directed at the object of the human body which is displayed tabooly in the form of "nude" and contains sexuality or intimacy. The work contains voyeuristic elements which often lead to negative perceptions or views and even behavioral deviations. disinterestedness attitude, thus, as answering the problem. the researcher tries to first explain the description of voyeuristic in a work of Newton's identical voyeuristic example. After that put forward a critical view of the use of disinterestedness attitude to interpret voyeuristic works. The method used is a phenomenological approach. The result of this analysis is the view of disinterestedness implying that selfless and selfless use can capture the value of the beauty of a work but in the existence of voyeuristic art it turns out that the effect is great if these two things are separated. Disinterestedness seems to encourage interpreters to create impersonal personalities in order to capture the "aesthetic" value of a work by capturing the other side of nudity. However, the value of a work cannot be separated from the truth it depicts.